Reduced Gait Variability and Enhanced Brain Activity in Older Adults With Auditory Cues: A Functional Near-Infrared Spectroscopy Study. (November 2018) - Vitorio, Rodrigo; Stuart, Samuel; Gobbi, Lilian T. B.; Rochester, Lynn; Alcock, Lisa; Pantall, Annette
Background . Aging is associated with declining mobility, which negatively affects quality of life and incurs substantial economic costs. Techniques to maintain safe mobility in older adults are therefore essential. Rhythmic auditory cueing (RAC) can improve walking patterns in older adults. However, the neural correlates associated with RAC, how they are influenced by repeated exposure and their relationships with gait response, cognitive function, and depressive symptoms are unclear. Objectives . This study aimed to investigate the effects of RAC during walking on cortical activation and the relationship between RAC-related cortical changes and cognitive function, depressive symptoms, and gait response. Methods . Seventeen young adults and eighteen older adults walked on a motorized treadmill for 5 minutes (5 trials with alternating 30-second blocks of usual walking and RAC walking). Changes in oxygenated hemoglobin (HbO2 ) in the frontal cortex were recorded using functional near-infrared spectroscopy. Cognitive domains were assessed through validated tests. A triaxial accelerometer measured gait parameters. Results . Gait variability decreased and prefrontal HbO2 levels increased during cued walking relative to usual walking. Older adults showed greater HbO2 levels in multiple motor regions during cued walking although the response reduced with repeated exposure. In older adults, lower depression scores, higher cognitive functioning, and reduced gait variability were linked with increased HbO2 levels during RAC walking. Conclusion . These findings suggest that walking improves with RAC in older adults and is achieved through increased activity in multiple cortical areas. The cortical response decline with repeated exposure indicates older adults' ability to adapt to a new task.